Relationship between the numbers of iron tablets received and of iron tablets consumed with the birth length at Aisyiyah Hospital, Bojonegoro - Firdaus, Desiana; Sudalhar, Sudalhar; Ningtias, Rina Hidayatin (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2025)
Background: Birth length is one of the risk factors for stunting in toddlers in the future. Stunting is a condition where a child's height is not by their age, which is indicated by a z score <-2 SD. Stunting can occur since the baby is in the womb, or in the first 1000 days of life which is indicated by a birth length of <48 cm.Objective: The purpose of this study was to examine the relationship between iron supplementation and birth length at Aisyiyah Hospital, Bojonegoro.Materials and Methods: The study respondents were 81 mothers and babies who were in the postpartum room of Aisyiyah Hospital, Bojonegoroduring the period from March to April 2024. Data on the number of iron tablets received and consumed were obtained from interviews with respondents, and the baby's birth length was obtained from data on the patient's medical records.Results: The study’s results showed that the prevalence of short birth length (stunting) at Aisyiyah Hospital, Bojonegoro was 38.8%. Based on the results of the correlation test conducted with Spearman rho, it was found that there was a significant relationship between the number of iron tablets received and the number of iron tablets consumed with the length of the baby's birth, as indicated by the p-value and r value respectively (p = 0.013; r = 0.439) (p = 0.005; r = 0.496).Conclusion: This study shows a significant relationship between the number of iron tablets received and the number of iron tablets consumed with the length of the baby's birth.